The Enhancement of Higher Right Faith in the Buddha's Virtues Appeared in Sampasadaniya Sutta - Boonchoo, Phra Wisut Kamalo; Koomkrong, Viroj (Journal of Dhamma for Life, 2025)
This thesis aims to study the profound faith in the virtues of the Buddha through an analysis of the Sampasādanīya Sutta, a significant discourse in Theravāda Buddhism. The study has three objectives to examine the structure and core content of the Sampasādanīya Sutta To study the development of faith in the Buddha’s virtues based on Theravāda Buddhist scriptures and to investigate the modes of generating faith in the Buddha’s virtues as presented in the Sampasādanīya Sutta. The research employs documentary research methodology by collecting and analyzing data from Theravāda Buddhist scriptures and relevant documents. The analysis is conducted using a systematic descriptive approach The research findings reveal that the Sampasādanīya Sutta is a discourse delivered by Venerable Sāriputta in the presence of the Buddha at Nālandā in the kingdom of Magadha. Its purpose was to express profound reverence for the Buddha by extolling his qualities in terms of Dhamma exposition, purity, wisdom, and great compassion. These are reflected through praises declaring the Buddha as an excellent expounder of Dhamma, one who attained enlightenment by himself, and a teacher of all beings The nine attributes of the Buddha (Buddhaguṇa) are categorized into three main groups Virtues of Purity, such as Arahaṃ, Vijjācaranasampanno, Bhagavā, Virtues of Wisdom, such as Sammāsambuddho, Lokavidū, Buddho and Virtues of Great Compassion, such as Sugato, Anuttaro, Satthā Devamanussānaṃ The modes of generating profound faith in the Buddha’s virtues according to the Sampasādanīya Sutta are divided into six categories The exposition of seven groups of wholesome qualities, such as the Four Foundations of Mindfulness (Satipaṭṭhāna) and the Four Bases of Spiritual Power (Iddhipāda) The presentation of six pairs of sense bases The explanation of the miracle of instruction (Ādesanāpāṭihāriya) The description of the Four Attainments of Vision (Dassanasamāpatti)The explanation of the Seven Factors of Enlightenment (Bojjhaṅga) with diligence; and The exposition of the Four Noble Paths of Practice (Paṭipadā).